ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL PADA SISWA KELAS VIII MTs DI KABUPATEN BANDUNG BARAT - Akbar Hanipa; Veny Triyana Andika Sari (Departement of Mathematics Education, 2019)
This study aims to describe the mistakes made by students and analyze the factors that cause student errors in completing in SPLDV material. The method used in this study is descriptive qualitative. This research took place in the eighth grade Al Barry MTs cikalong wetan in the 2018/2019 academic year. The population of this study was all eighth grade students of junior high / MTs in the western Bandung regency who had studied SPLDV material. The research subjects were class VIII A students at MTs Al Barry cikalong wetan. Data collection techniques using test and interview methods. The steps of analysis include data reduction, data presentation, and verification. Based on the results of data analysis it can be concluded that in solving SPLDV problems making mistakes; (1) Concept errors, (2) errors in understanding questions, (3) calculation errors. The causative factor is the students' understanding ability which is low in mastering the concept, lack of training in completing varied questions, hurrying and not being careful in solving problems.